Natural error patterns enable transfer of motor learning to novel contexts - Torres-Oviedo, Gelsy (American Physiological Society, 2012)
Successful behavior demands motor learning to be transferable in some cases (e.g., adjusting walking patterns as we develop and age) and context specific in others (e.g., learning to walk in high heels). Here we investigated differences in motor learning transfer in people learning a new walking pattern on a split-belt treadmill, where the legs move at different speeds. We hypothesized that transfer of the newly acquired walking pattern on the treadmill to natural over ground walking might depend on the pattern of errors experienced during learning. Error patterns within a person's natural range might be experienced as endogenous (i.e., produced by the body), encouraging general adjustments that transfer across contexts. On the other hand, larger errors might be experienced as exogenous (i.e., produced by the environment), indicating unusual conditions requiring context-specific learning. To test this, we manipulated the distribution of errors experienced during learning to lie either within or outside the normal distribution of walking errors. We found that restriction of errors to the natural range produced transfer of the new walking pattern from the treadmill to natural walking off the treadmill, while larger errors prevented transfer. This result helps explain how transfer of motor learning is controlled, and it offers an important strategy for clinical rehabilitation, where transfer of motor learning to other contexts is essential.